Consumers behavior on organic food: Evidence from the Republic of Serbia - Vehapi Semir; Dolićanin Edin (Ekonomika Poljoprivrede (1979), 2016)
In developed countries, the demand for organic food has seen a significant increase in the past decade. However, the organic food market in Serbia is still in its infancy and can be considered an emerging market. By gaining an understanding of consumer behavior on the Serbian market, it is possible to provide a greater consumption of organic food per capita through an appropriate marketing approach, as well as quicker development of the national market. This paper will outline some of the most significant findings obtained from a quantitative study of the population of Serbia in the role of buyers and potential buyers of organic food. How much knowledge respondents have about organic food was also studied and presented here, as was the socio-demographic profile of the consumers as an important determinant of organic food consumption. In addition, we also analyzed consumer behavior when buying organic food from the standpoint of basic instruments of the marketing mix: the product, the price, marketing communication (promotion) and marketing channels (place). The obtained results were explained in relation to the theoretical knowledge obtained from previous studies carried out on various national markets. Based on these findings, a solid foundation for the development of effective marketing strategies was obtained.